Søren Kierkegaard’s Category of Repetition in the Teachings of Jacques Lacan - Olszewska, Emilia (Folia Philosophica, 2024)
In this article, I explore how the category of repetition, as developed in the philosophical writings of Søren Kierkegaard, is applied in the psychoanalytic teachings of Jacques Lacan, particularly as presented in the transcriptions of his seminars and the collection of his writings, Écrits. First, I examine how Lacan accounts for the functioning of the neurotic symptom drawing on Kierkegaard’s opposition of recollection and repetition. I then show how references to Kierkegaard’s Repetition inform Lacan’s conceptualisation of the three orders: the Real, the Symbolic, and the Imaginary (RSI). Finally, I summarise the evolution of Lacan’s theoretical positions on the phenomenon of repetition within the context of the psychoanalytic clinic, and consider their relationship to the concept of repetition in Søren Kierkegaard’s philosophy.